Distribution and function of prokaryotes involved in mercury methylation, demethylation, and reduction in the western North Pacific Subtropical Gyre - Tada, Yuya; Nakajima, Ryota; Kitamura, Minoru; Marumoto, Kohji (Frontiers in Microbiology, 2026)
Methylmercury (MeHg), a bioaccumulative neurotoxic heavy metal, substantially threatens environmental and human health. In natural environments, MeHg formation and degradation are primarily mediated by microorganisms containing hgcAB, merA, or merB genes. However, these genes have not been simultaneously analyzed in open-ocean samples. This study aimed to investigate the distribution and phylogeny of functional genes associated with mercury (Hg) methylation (hgcA and hgcB), demethylation (merB), and reduction (merA), as well as dissolved total Hg (THg) and MeHg concentrations in the western North Pacific Subtropical Gyre (WNPSG) using metagenomic analysis. Although THg levels varied across sampling sites, MeHg concentrations consistently increased with depth. A strong correlation between dissolved MeHg and apparent oxygen utilization indicated a link between Hg methylation and microbial respiration. hgcA, merB, and merA were predominantly detected at depths of 500–1,500 m, where MeHg concentrations peaked, indicating active microbial Hg speciation within mesopelagic layers. A higher abundance of hgcA than merB suggests that microbial Hg methylation may surpass demethylation in this region. Phylogenetic analyses of hgcAB identified the Nitrospina lineage as dominant Hg methylators. Metabolic pathway analyses of metagenome-assembled genomes (MAGs) showed that Nitrospina harboring hgcAB possesses the nitrite reductase pathway, suggesting a linkage between Hg methylation and nitrogen cycling. MAGs with hgcA affiliated with Myxococcota (Deltaproteobacteria) exhibited a strong association with sulfur cycling. Diverse lineages harboring merB and merA genes were identified, suggesting that MeHg demethylation and Hg(II) reduction likely co-occur. Methanogenesis pathways in some Alphaproteobacteria with merB or merA suggest a potential connection between methane production and MeHg degradation and Hg(II) reduction. These findings provide novel insights into the intricate interactions between microbial communities, functional gene distributions, and Hg biogeochemical cycling in the WNPSG.